Pengaruh Variasi Penambahan Naoh Pada Kuat Tekan Mortar Geopolimer Abu Terbang Dengan Opc Sebagai Tambahan - Ferisma Ratu Giri; Monita Olivia; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study investigates the effect of NaOH molarity on geopolymer mortar with Ordinary Portland Cement in addition to geopolymer mortar. The intent of using Ordinary Portland Cement is to produces hybrid geopolymer concrete which can harden without high temperatures. Mortar was treated at room temperature (20-25 0C), then testing after mortars aged 7 and 28 days. The variation of molarity of NaOH used was 10 M, 12 M, and 14 M, while the ratio of silicate modulus, Ms ( Na2SiO3 / NaOH) and the percentage of OPC added to the mixture were 2,5 and 15% of the weight of fly ash, respectively compressive test was conducted to the specimens. The results showed that mortar with 12M NaOH had a compressive strength of 15,47 MPa, while the compressive strength of specimens with 8M, 10M, 14M and 16M were 10,93 MPa, 14 MPa, 13,20 MPa and 10,67 MPa, respectively. The optimal compressive strength is obtained on addition 12M NaOH. Keywords: Compressive strength testing, geopolymer, hybrid geopolymer, mortar, NaOH molarity, silicate modulus ratio, ordinary portland cement..